2020
DOI: 10.1002/pts.2506
|View full text |Cite
|
Sign up to set email alerts
|

Packaging paper with improved mechanical and oil absorption properties based on novel ingredients

Abstract: A novel cost‐saving coat was applied on paper sheets to enhance their air, water vapor, and oil resistance to be used in the packaging purposes. This coat is based on new ingredients including core‐shell pigment CoO.ZnO/SiO2, which is composed of silica fume waste comprising 80% of the new pigment covered with the chemically and thermally stable binary oxide of CoO.ZnO with very low cobalt oxide content. This pigment was bind to the cellulosic fibers using sodium alginate, which is now broadly used due to its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…Table 3 shows that with increasing the concentration of SEDCFs, the maximum load and breaking length were increased; this was due to the strong coated HSP formed by the action of coating agent. This result is in agreement with other work 58 . The tensile index is (tensile strength/base weight) a mechanical variable that characterizes tensile strength in relation to material quantity.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Table 3 shows that with increasing the concentration of SEDCFs, the maximum load and breaking length were increased; this was due to the strong coated HSP formed by the action of coating agent. This result is in agreement with other work 58 . The tensile index is (tensile strength/base weight) a mechanical variable that characterizes tensile strength in relation to material quantity.…”
Section: Resultssupporting
confidence: 94%
“…The oil resistance of paper coated with different SEDCFs concentration exhibited good oil resistance as the SEDCFs concentration increased from (1–3%) due to the high hydrophobicity of it, which meets the demands for food packaging. Several studies were reported, the addition of active materials as coated part enhance their ORB as cellulose nanofibers/chitosan nanoparticles 65 , HSP/ZnO/SiO2 58 and HSP/Microcrystalline Wax Emulsion 66 .…”
Section: Resultsmentioning
confidence: 99%
“…Alginates are naturally occurring indigestible polysaccharides. They are commonly produced from various genera of brown algae [223]. A lot of research on alginate has focused on edible coatings or to improve color and flavors [224,225].…”
Section: Alginatesmentioning
confidence: 99%
“…The network created by SA film blended with (CoO.ZnO/SiO 2 ) pigments on paper sheet substrate drastically changed their mechanical and barrier properties. They are highly dense and organized, causing the creation of smooth distribution of nanoparticles and a strong surface that fills the pores in the paper matrices and increases the air, water vapor, and oil resistance of the samples coated with SA-CoO.ZnO/SiO 2 pigments compared with uncoated paper [223].…”
Section: Alginatesmentioning
confidence: 99%
“…The network created by SA film blended with (CoO.ZnO/SiO2) pigments on paper sheet substrate drastically changed their mechanical and barrier properties. They are highly dense and organized, causing the creation of smooth distribution of nanoparticles and a strong surface that fills the pores in the paper matrices and increases the air, water vapor, and oil resistance of the samples coated with SA-CoO.ZnO/SiO2 pigments compared with uncoated paper [223].…”
Section: Alginatesmentioning
confidence: 99%